Advanced Glycation End Products:Receptors for Advanced Glycation End Products Axis in Coronary Stent Restenosis: A Prospective Study - Pearce, Colin; Islam, Naorin; Bryce, Robyn; McNair, Erick Donnell (International Journal of Angiology, 2018)
This study was aimed to correlate the pre- and 6-month postpercutaneous coronary intervention (PCI) serum concentrations of advanced glycation end products (AGE), soluble receptors for advanced glycation end products (sRAGE), AGE/sRAGE ratio, and serum malondialdehyde (MDA) levels with in-stent restenosis (ISR) among patients receiving either a drug-eluting stent (DES) or a bare-metal stent (BMS).In-stent restenosis remains as an adverse outcome following PCI. Sixty consecutive nondiabetic, Caucasian male patients, diagnosed with a non-ST-elevation myocardial infarction who received either a DES or BMS via PCI, were enrolled. Baseline levels of serum AGE, sRAGE, AGE/sRAGE ratios, MDA, and angiographic parameters were determined at stenting and at 6 months. Patients with and without ISR at 6 months were compared on both baseline and 6-month biomarker levels and within stent types.The pre-PCI serum AGE levels and AGE/sRAGE ratios were higher in ISR patients compared with non-ISR patients, while the pre-PCI and post-PCI serum sRAGE levels were lower in ISR patients compared with non-ISR patients. The pre and post-PCI levels of MDA were also higher in ISR patients. Comparing stent types, relative levels of MDA between those with and without ISR at the respective time points were similar, although changes between time points appeared type specific.Post-PCI ISR correlates with low serum values of sRAGE and high serum values of AGE, MDA, and AGE/sRAGE ratio which are present at stenting. The associations of baseline AGE, sRAGE, AGE/sRAGE, and MDA levels with ISR appear consistent between stent types.
Keywords: PCI; stent; restenosis; cardiac Biomarkers; advancedglycation end products; soluble receptor for advanced glycation end products; oxidative stress